Exopolysaccharides from extremophiles: from fundamentals to biotechnology - TOKSOY ÖNER, EBRU (TAYLOR & FRANCIS LTD, 2010)
Exopolysaccharides (EPSs) make up a substantial component of the extracellular polymers surrounding most microbial cells in extreme environments like Antarctic ecosystems, saline lakes, geothermal springs or deep sea hydrothermal vents. The extremophiles have developed various adaptations, enabling them to compensate for the deleterious effects of extreme conditions, e.g. high temperatures, salt, low pH or temperature, high radiation. Among these adaptation strategies, EPS biosynthesis is one of the most common protective mechanisms. The unusual metabolic pathways revealed in some extremophiles raised interest in extremophilic microorganisms as potential producers of EPSs with novel and unusual characteristics and functional activities under extreme conditions. Even though the accumulated knowledge on the structural and rheological properties of EPSs from extremophiles is still very limited, it reveals a variety in properties, which may not be found in more traditional polymers. Both extremophilic microorganisms and their EPSs suggest several biotechnological advantages, like short fermentation processes for thermophiles and easily formed and stable emulsions of EPSs from psychrophiles. Unlike mesophilic producers of EPSs, many of them being pathogenic, extremophilic microorganisms provide non-pathogenic products, appropriate for applications in the food, pharmaceutical and cosmetics industries as emulsifiers, stabilizers, gel agents, coagulants, thickeners and suspending agents. The commercial value of EPSs synthesized by microorganisms from extreme habitats has been established recently.
Keywords: exopolysaccharide; sugar composition; extremophile; exopolysaccharide production; ecology; EXTRACELLULAR POLYMERIC SUBSTANCES; DELBRUECKII SUBSP BULGARICUS; ARCHAEON THERMOCOCCUS-LITORALIS; XANTHAN GUM PRODUCTION; SP-NOV.; BACTERIAL EXOPOLYSACCHARIDES; EXOCELLULAR POLYSACCHARIDE; HYDROTHERMAL VENTS; GEN.-NOV.; GROWTH